Taking the sting out of disease diagnosis - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Diagnosis of honey bee diseases 1991 53pp United States Department of Agriculture Handbook 690 National Technical Information Service, 5258 Port Royal Road Springfield, VA 22161, USA